N-Acetylcysteine Improves Renal Function and Reduces Tissue Malondialdehyde Levels in Glycerol-Induced Acute Kidney Injury - Suhartati; Hasanatuludhhiyah, Nurina; Ratnani, Arifian Hardi Putri (Current Internal Medicine Research and Practice Surabaya Journal, 2023)
Introduction: The etiology of myoglobinuric acute kidney injury involves oxidative injury brought on by the Fenton reaction and myoglobin redox cycle. Renal tubules may be harmed, and lipid peroxidation compounds with vasoconstrictor characteristics may be produced. N-acetylcysteine (NAC) is an antioxidant shown to improve renal microcirculation and have protective effects in various models of renal damage. The aim of the study was to demonstrate the protective impact of NAC in glycerol-induced rats by measuring tissue malondialdehyde (MDA) level and renal function test (RFT), and to determine the correlation between the protective effect and NAC dose.Methods: This study measured tissue malondialdehyde (MDA) and renal function to examine any protective effect of NAC in a glycerol-induced rat model and to determine whether the effect was dose-related. Five groups of male Wistar rats were used: 1) saline control group, (2) glycerol (50%, 8mL/kg, i.m) plus saline i.v group, 3) glycerol plus NAC (100 mg/kg)-treated group, 4) glycerol plus NAC (200 mg/kg)-treated group, 5) glycerol plus NAC (400 mg/kg)-treated group. At 24 hrs, after glycerol injection, rats were sacrificed, cardiac blood was taken for renal function measurement, and renal tissues were removed for thiobarbituric acid MDA level assessment.Results: Our study revealed that glycerol administration significantly amplified renal tissue MDA, serum creatinine, and BUN (blood urea nitrogen) levels. However, NAC administration dampened the MDA increment and renal function deterioration (p<0.05). Moreover, tissue MDA, BUN, and serum creatinine levels were significantly correlated to NAC dose (r=0.485; r=0.491; rs=0.544, respectively; all p<0.05), indicating that NAC protection declines by dose increments.Conclusion: In this glycerol-induced acute kidney injury rat model, the administration of intravenous NAC 100 mg/kg reduced lipid peroxidation and improved renal function. Nevertheless, the protective effect was diminished in higher doses.